A dataset of ground-based vertical profile observations of aerosol, NO2, and HCHO from the hyperspectral vertical remote sensing network in China (2019–2023) - P. Jiao; C. Xing; Y. Li; X. Ji; W. Tan; Q. Li; H. Liu; C. Liu; C. Liu; C. Liu; C. Liu (Earth System Science Data, 2025)
Vertical profile observations of atmospheric composition are crucial for understanding the generation, evolution, and transport of regional air pollution. However, existing technological limitations and costs have resulted in a scarcity of vertical profile data. This study introduces a high-time-resolution (approximately 15 min) dataset of vertical profile observations of atmospheric composition (aerosol, NO2, and HCHO) conducted using passive remote sensing technology across 32 sites in 7 major regions of China from 2019–2023. The study meticulously documents the vertical distribution, seasonal variations, and diurnal pattern of these pollutants, revealing long-term trends in atmospheric composition across various regions of China. This dataset provides essential scientific evidence for regional environmental management and policymaking. Its sharing would facilitate the scientific community in exploring source–receptor relationships, investigating the impacts of atmospheric composition on regional and global climate and feedback mechanisms. It also holds potential for enhancing satellite retrieval methods and advancing the development of regional transport models. The dataset is available for free at Zenodo (https://doi.org/10.5281/zenodo.15211604, Jiao et al., 2024).